FORMATION OF EMOTIONAL STABILITY AS AN IMPORTANT INDICATOR OF EMOTIONAL CULTURE OF FUTURE TEACHERS - Hordiyenko, N.V. (Pedagogy of Higher and Secondary Education, 2009)
The part and the functions of emotions as a necessity of harmonizing of interaction of emotional and intellectual factors during studying process as an important means of rising of effectiveness of a methodic work for quality education are being substantiated in the article.